Sarah Gamp - the role of the domiciliary nurse in literature - Scerri, Mariella (Research and Humanities in Medical Education, 2021)
Hospitals in Britain during the Victorian period became increasingly involved with the education of health care professionals. Yet, despite the growing role of hospitals, there were wide variations in the quality of medical services available. This allowed for significant consequential choices and advancement to be made, though it was mainly in the medical sector. Campaigning through the Doctor’s Registration Movement also left its mark in a social climate considered turbulent. Remarkably, nursing as a profession received almost invisible treatment as is seen from the feeble echo in the vast expanse of literature from that time. Acknowledging nursing’s historical point of entry into the discourse, and its journey from the Medieval Period right through the Victorian era is paramount. However, this cannot be properly done without giving due emphasis to the community nurse. Examining the historical terrain and the historical influences that led to the demise of community nursing, through Dickens’s fictional portrayal of Sarah Gamp, this paper will provide answers on the present status of this aspect of the nursing profession. It will offer a close reading of Dickens’s Sarah Gamp from Martin Chuzzlewit, and it will try to explore and elicit factual information from a rich and impressively extensive fictional plot. This paper also offers an analytical exposition of Gamp’s peculiar potential for the reading of the nurse figure as unconstrained by Victorian codes of gender and economics.